Parental Distress and Stress in Association with Health-Related Quality of Life in Youth with Spina Bifida: A Longitudinal Study. Issue 9 (December 2018) - Driscoll, Colleen F. Bechtel; Buscemi, Joanna; Holmbeck, Grayson N.
Abstract: Objective: This study examined associations between 3 distinct parent factors (parent personal distress, parenting stress, and spina bifida (SB)-specific parenting stress) and youth and parent proxy reports of youth health-related quality of life (HRQOL) over time. Method: Participants were recruited as part of a longitudinal study, and data were collected at 3 time points, spaced 2 years apart. Parents and youth completed questionnaires, and youth completed neuropsychological assessment tasks to determine youth intelligence quotient during home visits. Results: Analyses revealed that higher levels of maternal SB-specific parenting stress were related to lower levels of youth-reported HRQOL at time 1. Other parent factors were not associated with youth report of HRQOL at the earlier time points, although higher levels of maternal SB-specific parenting stress and paternal parenting stress were associated with lower levels of youth HRQOL at time 3. For mothers and fathers, increased parent personal distress, parenting stress, and SB-specific parenting stress were associated with decreased proxy report of youth HRQOL. Of these three parent factors, SB-specific parenting stress was consistently the most strongly associated with parent proxy-report of youth HRQOL. Conclusion: Parenting stress and distress are important targets for interventions, and these interventions may improve youth outcomes, especially as youth age. Future research is needed to identify other factors influencing youth HRQOL over time.